Preparation of cellulose with controlled molecular weight via ultrasonic treatment improves cholesterol‐binding capacity. Issue 2 (5th December 2019) - Yan, Ling; Liu, Bing; Liu, Changhong; Qu, Hao; Zhang, Zhengzhu; Luo, Jianping; Zheng, Lei
Abstract: The effect of ultrasonic treatment was evaluated to develop an efficient preparation method of cellulose with controllable molecular weight (Mw) and preferable functional properties. Our results showed that the physical approach could prominently reduce the mean Mw of cellulose from 68.07 to 6.82 KDa via 30‐hr ultrasonic treatment. The morphology and structure of the samples were characterized using Fourier transform infrared spectroscopy, X‐ray diffraction, scanning electron microscope ( SEM ), and laser diffraction, indicating a slight change in structure and notable modification in morphology caused by ultrasonic treatment. Interestingly, the ultrasonic‐treated cellulose exhibited much better physicochemical properties. For example, with a 30‐hr ultrasonic treatment, the cholesterol‐binding capacities of cellulose were increased about 2.42‐fold at pH 7.0 and 1.96‐fold at pH 2.0. The findings demonstrated that cellulose treated by ultrasonic processing could have a great potential for applications in the biomedical and food industries. Practical applications: As a major source of insoluble fiber, cellulose has already been recommended for its possible benefits to human health, leading to numerous efforts for its applications in food industry and biomedical engineering. In this work, we successfully controlled Wm of cellulose via ultrasonic treatment, and the ultrasonic‐treated cellulose exhibited improved functional and physicochemical properties. The positive effect of ultrasound may be useful for functional modification and utilization of cellulose.